مسح الفطريات الكيراتينية في غبار أرضيات بعض مدارس مدينة العمارة - حسين صالح طلال (University of Thi-Qar Journal of Science, 2011)
Eighty floor dust samples were collected from some schools in Amarh city to investigate the presence of Keratinophilic fungi using hair- baiting technique . Twenty six species of fungi belonging to twelve genera were isolated and identified The fungi included : six species from the genus chrysosporium ,five species from the genus Microsporum , foure species from the genus Trichophyton , three species from the genus Aspergillus and one species of the following genera : Alternaria, Cladosporium , Drechslera , Fusarium , Mucor , Penicillium , Scopulariopsis and Scytlidium .On the other hand the haemolytic of some species were tested in vitro using blood agar culture ,among them Aspergillus flavus was more efficienty than other . تم جمع ) 41 ( عينة غبار أرضية بعض مدارس مدينة العمارة لمبحث عن تواجد الفطريات الكي ا رتينية فييا وقد استخدمت طريقة الطعم الكي ا رتيني لعزل ىذه الفطريات . تم عزل وتشخيص ) 62 ( نوعاً تعود إلى ) 06 ( جنساً وكان أكثرىا ظيو ا رً جنس Chrysosporium )ستة أنواع( ، Microsporum )خمسة أنواع(، Trichophyton )أربعة أنواع (، Aspergillus )ثلاث أنواع(، )ونوع واحد( لكل من الأجناس : Alternaria ، Cladosporium ، Drechslera ، Fusarium ، Mucor ، Penicillium ، Scopulariopsis و Scytalidium . اختبرت قدرة بعض الفطريات المعزولة عمى حل الدم عمى الوسط أكار الدم وكان الفطر A . flavus أكثرىا قدرة عمى ذلك .